Faktor-Faktor yang Mempengaruhi Kejadian Asfiksia Di RSUD Majene - sitti aras diana (Jurnal Kesehatan Marendeng, 2023)
Neonatal asphyxia is a condition where the baby cannot breathe spontaneously and regularly after birth. This type of research is analytical observational with a case control approach. This research was conducted at the Majene Hospital with a sample of 66 babies who met the inclusion criteria using the total sampling method. The independent variables of this research are age, parity, gestational age, type of delivery and uses a checklist measuring instrument. The research results from the chi square test results showed that there was no significant relationship between the incidence of asphyxia and age with a p value of 0.438 > ꭤ 0.05, there was no significant relationship between the incidence of asphyxia and parity with a p value of 0.248 > ꭤ 0 .05, there is no significant relationship between the incidence of asphyxia and gestational age where the p value is 0.592 > ꭤ 0.05 and there is no significant relationship between the incidence of asphyxia and the type of delivery p value 0.125 > ꭤ 0.05. The conclusion of this research is that there is no significant relationship between the incidence of asphyxia and age, parity, gestational age and type of delivery at Majene Hospital in 2022. Keywords: Asphyxia, age, parity, gestation age, type of delivery